2015
DOI: 10.1002/ejp.795
|View full text |Cite
|
Sign up to set email alerts
|

Establishing clinically meaningful severity levels for the Tampa Scale for Kinesiophobia (TSK‐13)

Abstract: TSK-13 severity levels were strongly associated with objective lifting performance variables and psychosocial PRO measures, providing support for these severity levels as a guideline for healthcare providers and researchers in interpreting TSK-13 scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 70 publications
1
51
0
2
Order By: Relevance
“…For example, our participants' kinesiophobia scores fell into the severe category (43-52 on the TSK) and were markedly higher compared to another study of 912 chronic pain sufferers whose scores fell into the moderate category (33-43). 34 Further, our chronic pain population suffered from more pain catastrophizing (higher PCS scores than the referenced study) than a group of 60 subjects from an outpatient chronic pain treatment group. 14,44,45 Additionally, our participants had higher depression scores (higher BECK scores than the referenced study), reported more severe subjective ratings of pain (higher MPQ scores than the referenced study), and more severe subjective perceptions of disability (higher PDI scores than the referenced study) than the previous literature in chronic pain populations.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…For example, our participants' kinesiophobia scores fell into the severe category (43-52 on the TSK) and were markedly higher compared to another study of 912 chronic pain sufferers whose scores fell into the moderate category (33-43). 34 Further, our chronic pain population suffered from more pain catastrophizing (higher PCS scores than the referenced study) than a group of 60 subjects from an outpatient chronic pain treatment group. 14,44,45 Additionally, our participants had higher depression scores (higher BECK scores than the referenced study), reported more severe subjective ratings of pain (higher MPQ scores than the referenced study), and more severe subjective perceptions of disability (higher PDI scores than the referenced study) than the previous literature in chronic pain populations.…”
Section: Discussionmentioning
confidence: 67%
“…Score categories for the TSK include: 13-22, subclinical; 23-32, mild; 33-42, moderate; 43-52, severe. 34…”
Section: Outcome Measures Tampa Scale Of Kinesiophobia (Tsk)mentioning
confidence: 99%
“…This result might reflect the progress of previous research regarding the psychometric properties of the different TSK versions. Compared to the 17-item version, the 13item version has better psychometric properties without the four inversely phrased items (Roelofs et al, 2004a;Neblett et al, 2016) and the 11-item version has been recommended for future research and clinical settings (for a chronological summary see Tkachuk and Harris, 2012).…”
Section: Fabq and Tskmentioning
confidence: 99%
“…The total score ranges from 13 to 52, with higher scores indicating higher fear and insecurity of movement (Cordeiro, Pezarat‐Correia, Gil, & Cabri, ). This scale has four severity ranges: “subclinical” (13–22);”mild” (23–32); “moderate” (33–42); and “severe” (43–52) (Neblett, Hartzell, Mayer, Bradford, & Gatchel, ).…”
Section: Methodsmentioning
confidence: 99%